Voltammetric Sensing of Nifedipine Using a Glassy Carbon Electrode Modified with Carbon Nanofibers and Gold Nanoparticles - Santos, Anderson M.; Wong, Ademar [UNESP]; Feitosa, Maria H. A.; Cardenas-Riojas, Andy A.; Calderon-Zavaleta, Sandy L.; Baena-Moncada, Angélica M.; Sotomayor, Maria D. P. T. [UNESP]; Moraes, Fernando C. (MDPI, 2023)
Nifedipine, a widely utilized medication, plays a crucial role in managing blood pressure in humans. Due to its global prevalence and extensive usage, close monitoring is necessary to address this widespread concern effectively. Therefore, the development of an electrochemical sensor based on a glassy carbon electrode modified with carbon nanofibers and gold nanoparticles in a Nafion® film was performed, resulting in an active electrode surface for oxidation of the nifedipine molecule. This was applied, together with a voltammetric methodology, for the analysis of nifedipine in biological and environmental samples, presenting a linear concentration range from 0.020 to 2.5 × 10−6 µmol L−1 with a limit of detection 2.8 nmol L−1. In addition, it presented a good recovery analysis in the complexity of the samples, a low deviation in the presence of interfering potentials, and good repeatability between measurements.
Keywords: carbon nanofibers; environmental samples; gold nanoparticles; nifedipine